The role of administrative supervision scope and the single window to increase the efficiency of investment (Case study: Sudanese Ministry of Investment) - عبده دسوقي ناندي ابو العلا; القراي عامر سالم الشيخ (Journal of Economics and Administrative Sciences, 2017)
Investment drives the wheel of the development of different developed and developing countries. Sudan is a model for a developing country facing a lot of difficulties in the field of both local and foreign investment. The present study was focused on the problem of poor diversification and efficiency of both local and foreign investment in Sudan. Also, it clarified the important role of administrative supervision to strengthen the efficiency of investment, taking the experience of the Sudan as a model. The researchers used the well-known descriptive and analytical tools (questionnaire, interview, observation) to complete this study. A well designed questionnaire was used. It included all questions that could cover all aspects of the subject of the study. In the present study 125 questionnaires were distributed among the target groups. Ninety one questionnaires were retrieved (73%) from the total distributed questionnaires. Data were statistically analyzed using SPSS program. In the present study, 62.3% of participants saw that the ministry of investment provides many methods that would simplify investment procedures. At the same time, 91.2% of participants assured that the ministry of investment applies a standard single window investment system in cooperation with other government agencies related to investment. Also, 83.9% of the respondents agreed that each job have an accurate and specific administrative supervision scope. Moreover, 90% of the respondents accepted that there are many external factors that may alter the scope of specific supervision. At the same time, 87.8% of the participants agreed that the ministry of investment provides a suitable environment for investment in Sudan, especially for foreign investment. Based on the obtained results, the study has proposed a set of recommendations to help simplify investment procedures especially: Periodical and continuous reviewing of the organizational structural system and job descriptions for managers and employees in the Ministry of investment by academics and specialists for continuous development. This is important to harmonize the international and local changes and avoid problems in the field of investment. We also stress on the importance of coordination among the relevant authorities. Developing more efficient modern communication tools and optimization of modern technology to simplify procedures for foreign and local investment. We also stress on the importance of quality control.